2008
DOI: 10.1017/s1121189x00002852
|View full text |Cite
|
Sign up to set email alerts
|

The Outcome Questionnaire 45.2. Italian validation of an instrument for the assessment of phychological treatments

Abstract: SummaryAims– The Outcome Questionnaire (OQ-45.2; Lambertet al., 2004) was designed to measure important areas of functioning (symptoms, interpersonal problems and social role functioning) that are of central interest in mental health. The crosscultural validity of the OQ-45.2 in the Italian population has been examined by comparing the psychometric properties and equivalence in factor structure and normative scores of the Italian OQ with the original American version.Method– Data were collected at university (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 25 publications
(36 reference statements)
1
20
0
4
Order By: Relevance
“…However, (i) the measurement model was invariant across genders, suggesting that - even if the sample was unbalanced - there were no gender differences in the factorial structure of the questionnaire, and (ii) we were largely interested in evaluating the factorial structure of ECR-12 in the general population and not a clinical sample. Finally, cut-off criteria from the OQ45.2 suggested that one third of our participants had significant levels of psychological distress, and the mean total scores among those who met the cutoff were comparable to mean scores reported by an Italian psychiatric sample (Chiappelli et al, 2008 ), increasing the validity of our findings.…”
Section: Discussionsupporting
confidence: 78%
“…However, (i) the measurement model was invariant across genders, suggesting that - even if the sample was unbalanced - there were no gender differences in the factorial structure of the questionnaire, and (ii) we were largely interested in evaluating the factorial structure of ECR-12 in the general population and not a clinical sample. Finally, cut-off criteria from the OQ45.2 suggested that one third of our participants had significant levels of psychological distress, and the mean total scores among those who met the cutoff were comparable to mean scores reported by an Italian psychiatric sample (Chiappelli et al, 2008 ), increasing the validity of our findings.…”
Section: Discussionsupporting
confidence: 78%
“…For example, Amble et al . () studied the psychometric properties of the Norwegian version of the OQ‐45 and compared their findings with the US, German (Moessner, Gallas, Haug, & Kordy, ), Italian (Chiappelli et al ., ; Lo Coco et al ., ), Swedish (Wennberg, Philips, & De Jong, ), Dutch (De Jong et al ., ) and Chinese (Qin & Hu, ) studies. Reported means, cut‐off scores and RCIs of clinical and non‐clinical populations varied substantially internationally.…”
Section: Introductionmentioning
confidence: 96%
“…Participants completed the Outcome Questionnaire (OQ 45.2) – Italian translation and validation [ 55 , 56 ] at entry to the study and at discharge from the hospital with a self-report procedure. At 6-month follow-up data have been collected via telephone during the tele-sessions.…”
Section: Materials and Methodologymentioning
confidence: 99%